2019
DOI: 10.1111/jora.12449
|View full text |Cite
|
Sign up to set email alerts
|

The New Biobehavioral Developmental Science of Puberty

Abstract: This special section is the product of a small-group meeting of those who study puberty and its relevance. Our aim was to gather information and write manuscripts to inform scientists of advances and continuing obstacles, as well as to stimulate interdisciplinary research on puberty relevant across the lifespan. The themes of the nine position or review papers (and commentary), range from cell to society. We hope this introduction will entice you to read all the papers and consider how they apply or expand you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
0
7
0
1
Order By: Relevance
“…Adolescence is defined as the physiological and psychological transition from childhood to adulthood, which begins with invisible hormonal changes signaling the onset of puberty (Ellison et al, 2012 ). It is a complex and dynamic period that is contextually and individually tailored, with maturation of the body and brain intimately linked to social status, location, culture, environment, and family circumstances (Dorn & Susman, 2019 ). Puberty is a short‐term biological event taking place over a few weeks (Bogin et al, 2018 ), although it is associated with a longer period of physiological changes ending in sexual maturation, and incorporating complex and interrelated hormonal processes, and the adolescent growth spurt (Ellison et al, 2012 ).…”
mentioning
confidence: 99%
“…Adolescence is defined as the physiological and psychological transition from childhood to adulthood, which begins with invisible hormonal changes signaling the onset of puberty (Ellison et al, 2012 ). It is a complex and dynamic period that is contextually and individually tailored, with maturation of the body and brain intimately linked to social status, location, culture, environment, and family circumstances (Dorn & Susman, 2019 ). Puberty is a short‐term biological event taking place over a few weeks (Bogin et al, 2018 ), although it is associated with a longer period of physiological changes ending in sexual maturation, and incorporating complex and interrelated hormonal processes, and the adolescent growth spurt (Ellison et al, 2012 ).…”
mentioning
confidence: 99%
“…Some studies conducted among Black boys report similar findings to those from research among White boys (Ge et al, 2003; Mendle et al, 2011), whereas other research has not found a link between early pubertal development and depressive symptoms (Carter, Leath, et al, 2017; Carter, Seaton, et al, 2017; Nadeem & Graham, 2005). Given that the physical changes associated with puberty tend to occur earlier among Black boys (Dorn & Susman, 2019), improved understanding about the nature of the relation between early pubertal development and depressive symptoms within this population is needed.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Impacts in early childhood have been linked to adult earnings and health outcomes (Richter et al, 2017). Throughout childhood and particularly in adolescence, compromised family function can increase risks of early marriage, death by suicide, substance abuse, road injuries, drowning, interpersonal violence, threats to their sexual and reproductive health and school dropout (Bearinger et al, 2007;Dorn & Susman, 2019;Patton et al, 2016;Viner et al, 2012). The consequences stretch to the next generation, as adolescents become parents with families of their own (Benny et al, 2017;Patton et al, 2016).The harm to children can have significant consequences for society as a whole.…”
Section: Costs Of Inactionmentioning
confidence: 99%